2021
DOI: 10.1016/j.jaccas.2020.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Sympathetic Denervation for Refractory Ventricular Arrhythmia in Continuous-Flow Left Ventricular Assist Device

Abstract: Cardiac sympathetic denervation has been shown to reduce sustained ventricular arrhythmias and implantable cardioverter-defibrillator shocks by inhibiting sympathetic outflow to the heart. We describe the first case to our knowledge of cardiac sympathetic denervation in the left ventricular assist device population. ( Level of Difficulty: Advanced. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…By decreasing sympathetic activity, sympathetic denervation has been shown to diminish the occurrence of persistent VA or the usage of ICD [ 59 ]. Vlismas et al [ 60 ] reported that sympathetic denervation was performed in 1 female patient with intermittent VA after LVAD implantation, and no recurrence was observed at the 8-month postoperative follow-up, implying that sympathetic denervation may be considered for patients with postoperative VA implanted with LVADs who are refractory to medical, ablative, or ICD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…By decreasing sympathetic activity, sympathetic denervation has been shown to diminish the occurrence of persistent VA or the usage of ICD [ 59 ]. Vlismas et al [ 60 ] reported that sympathetic denervation was performed in 1 female patient with intermittent VA after LVAD implantation, and no recurrence was observed at the 8-month postoperative follow-up, implying that sympathetic denervation may be considered for patients with postoperative VA implanted with LVADs who are refractory to medical, ablative, or ICD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Future treatment approaches and strategies for ventricular arrhythmias should include cardiac sympathetic denervation. Using this method, Vlismas et al 8 recently reported promising results in LVAD‐supported patients with ventricular arrhythmias who were unresponsive to pharmacological agents, catheter ablation or ICD therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Cardiac sympathetic denervation could also be a promising new therapeutic option for the management of recurrent ventricular arrhythmias. 11 Heart transplantation represents the optimal therapy for patients who experience refractory ventricular arrhythmias or VF during LVAD support. In this case, listing with a high priority status has to be considered timely if no other contraindications exist to avoid secondary organ damage.…”
Section: Discussionmentioning
confidence: 99%